Phylogeography of ancient and modern brown bears from eastern Eurasia. (25th February 2022) - Molodtseva, Anna S; Makunin, Alexey I; Salomashkina, Valentina V; Kichigin, Ilya G; Vorobieva, Nadezhda V; Vasiliev, Sergey K; Shunkov, Mikhail V; Tishkin, Alexey A; Grushin, Sergey P; Anijalg, Peeter; Tammeleht, Egle; Keis, Marju; et al.
Abstract: The brown bear ( Ursus arctos ) is an iconic carnivoran species of the Northern Hemisphere. Its population history has been studied extensively using mitochondrial markers, which demonstrated signatures of multiple waves of migration, arguably connected with glaciation periods. Among Eurasian brown bears, Siberian populations remain understudied. We have sequenced complete mitochondrial genomes of four ancient ( 4.5–40 kya) bears from South Siberia and 19 modern bears from South Siberia and the Russian Far East. Reconstruction of phylogenetic relationships between haplotypes and evaluation of modern population structure have demonstrated that all the studied samples belong to the most widespread Eurasian clade 3. One of the ancient haplotypes takes a basal position relative to the whole of clade 3; the second is basal to the haplogroup 3a (the most common subclade), and two others belong to clades 3a1 and 3b. Modern Siberian bears retain at least some of this diversity; apart from the most common haplogroup 3a, we demonstrate the presence of clade 3b, which was previously found mainly in mainland Eurasia and Northern Japan. Our findings highlight the importance of South Siberia as a refugium for northern Eurasian brown bears and further corroborate the hypothesis of several waves of migration in the Pleistocene.